New approach relevant to floor Nusselt number in floor heating system - Karadag, Refet; Teke, Ismail (PERGAMON-ELSEVIER SCIENCE LTD, 2008)
In this study, the Nusselt number over the floor is analysed numerically for different thermal conditions in a floor heated room. A new equation related to floor Nusselt number is developed. In the literature, there have been a number of equations, different from each other and appropriate only for the conditions at which the studies were performed, have been presented. While the mentioned equations were dependent only on the floor Rayleigh number, numerical data obtained in the current study show that the floor Nusselt number depends not only on the floor Rayleigh number but also the wall and ceiling Rayleigh numbers. Therefore, the new equation developed in the current study is a function of the Rayleigh numbers over the floor, wall and ceiling surfaces. This equation is compared with those found in the literature. It is seen that while the maximum deviation from the numerical data is 35% for the equations given in the literature, it is only 10% for the new equation. Therefore, the given equation is verified to be more reliable and appropriate for the calculation of Nusselt number. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: floor heating; natural convection; Nusselt number; Rayleigh number; THERMAL PERFORMANCE; TRANSFER COEFFICIENTS; ROOM; SIMULATION; CONVECTION; SURFACES; PLATE; Thermodynamics; Energy & Fuels; Mechanics